Opioid prescriptions before and after high-energy trauma - Zwisler, MD, PhD, Stine T.; Hallas, MD, PhD, Jesper; Larsen, MD, Morten S.; Handberg, MD, Gitte; Mikkelsen, MD, Soeren; Enggaard, MD, PhD, Thomas P. (Journal of Opioid Management, 2015)
Objective: To describe the legal use of opioids in adult patients before and after high-energy trauma. Design: The study was a retrospective database study. Setting: Clinical care outside hospitals. Patients: All patients who suffered high-energy trauma and were brought to Odense University Hospital (OUH), Denmark, in 2007 and 2008 were retrieved from the trauma database. These patients were linked with data on opioid use from the regional prescription database. In all, 938 patients were included. Main outcome measure: Redemption of opioid prescription during the 6 months prior to a multitrauma or redemption of two or more prescriptions for opioids 6 months or later after a multitrauma. Results: Of the 938 patients brought to OUH with severe trauma within the study period, 61 patients died (7 percent) and six of these had redeemed prescriptions for opioids within 6 months prior to the trauma (10 percent) compared to 65 patients of the 877 survivors (7 percent) (odds ratio 1.4, nonsignificant). In all, 62 patients (7 percent) redeemed opioid prescriptions later than 6 months after their trauma and in a multivariable analysis, severe injury itself and severe injuries of the lower extremities were associated with redemption of opioid prescription after the trauma. Conclusions: The authors did not find any correlation between death by trauma and redemption of opioid prescriptions within the 6 months before the trauma. More severe traumas and especially severe traumas to the lower extremities were associated with redemption of opioid prescriptions after multitrauma.